The impact of socioeconomic status on health functioning as assessed by the SF-36 questionnaire: the Whitehall II Study. - Hemingway, H (1997)
OBJECTIVES: This study measured the association between socioeconomic status and the eight scale scores of the Medical Outcomes Study short form 36 (SF-36) general health survey in the Whitehall II study of British civil servants. It also assessed, for the physical functioning scale, whether this association was independent of disease. METHODS: A questionnaire containing the SF-36 was administered at the third phase of the study to 5766 men and 2589 women aged 39 through 63 years. Socioeconomic status was measured by means of six levels of employment grades. RESULTS: There were significant improvements with age in general mental health, role-emotional, vitality, and social functioning scale scores. In men, all the scales except vitality showed significant age-adjusted gradients across the employment grades (lower grades, worse health). Among women, a similar relationship was found for the physical functioning, pain, and social functioning scales. For physical functioning, the effect of grade was found in those with and without disease. CONCLUSIONS: Low socioeconomic status was associated with poor health functioning, and the effect sizes were comparable to those for some clinical conditions. For physical functioning, this association may act both via and independently of disease.